Listening to Our Patients: Learning About Suicide Risk and Protective Factors From Veterans With HIV/AIDS. (December 2016) - Signoracci, Gina M.; Stearns-Yoder, Kelly A.; Holliman, Brooke Dorsey; Huggins, Joseph A.; Janoff, Edward N.; Brenner, Lisa A.
Purpose: We sought to gather perspectives of veterans with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) regarding suicide risk factors, warning signs, and protective factors. We also aimed to modify an existing Veterans Health Administration tool, the Suicide Risk Assessment Guide Pocket Card, for HIV/AIDS provider use. Methods: Twenty male veterans participated in audio-recorded semistructured interviews that were transcribed and coded for themes.Findings: Veterans highlighted personally relevant psychosocial stressors (i.e., poverty, social isolation and loneliness, and physical health). Although the concept of warning signs did not seem salient to participants, they named indicators of elevated imminent risk for self-directed violence (i.e., "relapse, " "not take'n medications, " and "miss'n appointments") and few protective factors. No themes emerged regarding recommended pocket card changes.Conclusions: This sample of veterans identified self-directed violence risks noted in the general population and others with HIV/AIDS, as well as proximal events associated with increased risk. Care providers are encouraged to explore the relevance of noted imminent and persistent indicators of increased risk with veterans seeking care.